Impactos das ações sociais na vida das pessoas que são atendidas pela igreja Adventista em Barcarena-PA - MOARES, Cleonice Tavares (2019)
The present paper deals with the impact of social actions outside the school environment, specifically in the Seventh-day Adventist Church of Central Barcarena. The interest in working on the social projects that are being developed in the Adventist Church came about specifically when I became aware of some people who had been assisted since childhood by the Adventurers Club, then by the Pathfinder Club - which are projects designed to serve the children of church and beyond - who today have a different life and attribute part of that change to the learning they gained during the time they were in those groups. This has aroused my deep interest because I am part of this social context, and understand how important this is for my future career as an education professional. Following this line of thought, I sought to understand the impacts that the social actions that are developed in the church cause in the lives of the people who are served by these projects. I also searched to examine how the work carried out in these projects contributes to the personal, social, intellectual and spiritual growth of each individual assisted, taking into account the vision of Social Pedagogy, as well as the social role of the Church in society. Based on this perspective, I will analyze the role of Social Pedagogy and the church in society, described by several authors, mainly GOHN (2006), Ellen White (2012) and Paulo Godinho (2013), who treat the gospel as an instrument for the salvation of people, as well as a means of help the needy as our teacher Jesus Christ has taught us. The methodological approach used to carry out the research was qualitative, being the data collection performed through semi structured interviews and questionnaires.Thisresearch has showed that the Church has a fundamental role in the participation and integral transformation of society, which goes far beyond evangelization. Therefore, it is evident that Pedagogy goes far beyond the walls of the school - that the pedagogical actions developed in other environments also have a positive and very marked impact on the lives of the people involved.